Small enterprise development in South Africa: The role of business incubators - Masutha Mukhove; Rogerson Christian M. (Bulletin of Geography. Socio-Economic Series)
Business incubation is a relatively new phenomenon in scholarship and policy development for small enterprise development. Business incubators offer targeted business support and technical support services to accelerate the growth of emerging and small start-up business enterprises into financially and operationally independent enterprises. South Africa has adopted business incubation as one vehicle for upgrading the SMME economy. This article examines the evolution of policy towards business incubation, current progress, institutional issues and emerging geographies of business incubators as part of the unfolding and dynamic SMME policy landscape in South Africa. Considerable differences are observed between the activities of the network of state-supported incubators as opposed to private sector operated incubators.